A multidisciplinary study using in vivo tumor models and microfluidic cell-on-chip approach to explore the cross-talk between cancer and immune cells. (October 2014) - Mattei, Fabrizio; Schiavoni, Giovanna; De Ninno, Adele; Lucarini, Valeria; Sestili, Paola; Sistigu, Antonella; Fragale, Alessandra; Sanchez, Massimo; Spada, Massimo; Gerardino, Annamaria; Belardelli, Filippo; Businaro, Luca; et al.
Abstract A full elucidation of events occurring inside the cancer microenvironment is fundamental for the optimization of more effective therapies. In the present study, the cross-talk between cancer and immune cells was examined by employing mice deficient (KO) in interferon regulatory factor (IRF)-8, a transcription factor essential for induction of competent immune responses. The in vivo results showed that IRF-8 KO mice were highly permissive to B16.F10 melanoma growth and metastasis due to failure of their immune cells to exert proper immunosurveillance. These events were found to be dependent on soluble factors released by cells of the immune system capable of shaping the malignant phenotype of melanoma cells. An on-chip model was then generated to further explore the reciprocal interactions between the B16.F10 and immune cells. B16.F10 and immune cells were co-cultured in a microfluidic device composed of three culturing chambers suitably inter-connected by an array of microchannels; mutual interactions were then followed using time-lapse microscopy. It was observed that WT immune cells migrated through the microchannels towards the B16.F10 cells, establishing tight interactions that in turn limited tumor spread. In contrast, IRF-8 KO immune cells poorly interacted with the melanoma cells, resulting in a more invasive behavior of the B16.F10 cells. These results suggest that IRF-8 expression plays a key role in the cross-talk between melanoma and immune cells, and under-score the value of cell-on-chip approaches as useful in vitro tools to reconstruct complex in vivo microenvironments on a microscale level to explore cell interactions such as those occurring within a cancer immunoenvironment.